Metode za ugotavljanje uspešnosti poslovanja visokošolskih knjižnic - Turk, Nana (visokošolska dela, 2006)
Libraries, as well as all non-profit organizations, evaluate their activities and services from several viewpoints using various methods of evaluation and measurement. Evaluation results represent an important source of information in the process of planning future activities. My Master's Thesis deals with the libraries of the University of Ljubljana and offers some new possibilities for evaluation activities among the libraries mentioned above, which were designed after examining their current conditions, readiness to cooperate on evaluation projects and practical solutions for different library systems described in literature assessing the quality of library services. The Thesis focuses on the library service quality survey - the assessment tool called LibQUAL+ designed by the Association of Research Libraries (ARL). LibQUAL+ was adapted from an established service quality survey known as SERVQUAL which was developed for private sector. It is based on gap theory and designed to measure minimum, perceived and desired expectations of service quality.
Keywords: knjižnice Univerze v Ljubljani; KUL; uspešnost delovanja; kazalci; kakovost; uspešnost; učinkovitost; efficiency; raziskovalne metode; LibQUAL+